A novel strategy via electrode catalysis induced nano transformation for lithiated-bimetallic-oxides to avoid the long activation process of advanced lithium-ion batteries. Issue 45 (11th November 2022) - Lu, Qiuchen; Dong, Youzhong; Fan, Qinghua; Kuang, Quan; Zhao, Yanming
Abstract : A simple and novel electrode modification scheme is revealed to effectively avoid long activation processes of high-energy transition metal oxide anode materials for the first time. Abstract : Improving the anode materials for lithium-ion batteries with a long activation process, poor cycle stability, and low Coulomb efficiency is of great significance for developing novel high-performance anode materials. Orthorhombic LiVMoO5 with high specific capacity was applied to the anode field of lithium-ion battery for the first time. However, the activation process led to its poor cyclic performance. By adopting a novel nano-transformation treatment process in a water and oxygen environment, we effectively avoided the long-term activation process. The specially treated LiVMoO5 electrode (STLVME) exhibited excellent reversible specific capacity (∼1100 mA h g −1 ) and rate cycle stability (capacity retention rate ∼100%). Furthermore, GITT and EIS also showed that compared with the primitive LiVMoO5 electrode (LVME), smaller internal resistance and a higher Li + diffusion coefficient were caused using the novel treatment process, significantly improving the rate cycle stability. Using in situ XRD and ex situ characterization, we illustrated the lithium storage mechanism of LVME and STLVME. In addition, the practical application potential of LVME and STLVME was also explored by assembling the full cells. Because the long-term activation process was effectively avoided, the full-cell exhibited amazing cycle stability, indicating that STLVME can be considered a promising potential anode for practical applications in energy storage devices.